Distribution of temperament/mizāj among patients with knee osteoarthritis: a cross-sectional study - Fouzia Farooq; Mir Idrees Hanief; Ghazala Javed; N. Zaheer Ahmed (International Journal Of Community Medicine And Public Health, 2026)
Background: Knee osteoarthritis (KOA) is a common degenerative joint disorder with multifactorial etiology. While established risk factors such as age, obesity, and mechanical stress are well known, constitutional factors like temperament (Mizāj) described in Unani medicine remain underexplored. Hence the present study was conducted to describe the distribution of Mizāj among patients with KOA. Methods: A hospital-based cross-sectional study was conducted at the Regional Research Institute of Unani Medicine (RRIUM), Srinagar, from April to October 2021. A total of 60 patients aged 40-70 years with clinically and radiologically confirmed KOA (Kellgren-Lawrence grade I and II) were included. Mizāj was assessed using a structured proforma based on classical Unani parameters. Data were analyzed using SPSS version 20.0. Descriptive statistics (frequencies and percentages) were calculated, and the Chi-square test was applied, with p